Duty versus distributive justice during the COVID-19 pandemic. (September 2021) - Shaibu, Sheila; Kimani, Rachel Wangari; Shumba, Constance; Maina, Rose; Ndirangu, Eunice; Kambo, Isabel
The COVID-19 pandemic exposed vulnerabilities in inadequately prioritized healthcare systems in low- and middle-income countries such as Kenya. In this prolonged pandemic, nurses and midwives working at the frontline face multiple ethical problems, including their obligation to care for their patients and the risk for infection with severe acute respiratory syndrome coronavirus 2. Despite the frequency of emergencies in Africa, there is a paucity of literature on ethical issues during epidemics. Furthermore, nursing regulatory bodies in African countries such as Kenya have primarily adopted a Western code of ethics that may not reflect the realities of the healthcare systems and cultural context in which nurses and midwives care for patients. In this article, we discuss the tension between nurses' and midwives' duty of care and resource allocation in the context of the COVID-19 pandemic. There is an urgent need to clarify nurses' and midwives' rights and responsibilities, especially in the current political setting, limited resources, and ambiguous professional codes of ethics that guide their practice.